Medication for Acromegaly Reduces Expression of MUC16, MACC1 and GRHL2 in Pituitary Neuroendocrine Tumour Tissue - Saksis, Rihards; Silamikelis, Ivars; Laksa, Pola; Megnis, Kaspars; Peculis, Raitis; Mandrika, Ilona; Rogoza, Olesja; Petrovska, Ramona; Balcere, Inga; Konrade, Ilze; Steina, Liva; Stukens, Janis; et al. (Frontiers in Oncology, 2021)
Acromegaly is a disease mainly caused by pituitary neuroendocrine tumours (PitNETs) overproducing growth hormone. First-line medication for this condition is the use of somatostatin analogues (SSAs), that decrease tumour mass and induce antiproliferative effects on PitNET cells. Dopamine agonists (DAs) can also be used, if SSA treatment is not effective. This study aimed to determine differences in transcriptome signatures induced by SSA/DA therapy in PitNET tissue. We selected tumour tissue from twelve patients with somatotropinomas, with half of the patients receiving SSA/DA treatment before surgery, and the other half treatment naive. Transcriptome sequencing was then carried out to identify differentially expressed genes (DEGs) and their protein-protein interactions, using pathway analyses. We found 34 upregulated and six downregulated DEGs in patients with SSA/DA treatment. Three tumour development promoting factors MUC16, MACC1 and GRHL2, were significantly downregulated in therapy administered PitNET tissue, this finding was supported by functional studies in GH3 cells. Protein-protein interactions and pathway analyses revealed extracellular matrix involvement in the antiproliferative effects of this type of the drug treatment, with pronounced alterations in collagen regulation. Here, we have demonstrated that somatotropinomas can be distinguished based on their transcriptional profiles following SSA/DA therapy, and SSA/DA treatment does indeed cause changes in gene expression. Treatment with SSA/DA, significantly downregulated several factors involved in tumorigenesis, including MUC16, MACC1 and GRHL2. Genes that were upregulated, however, did not have a direct influence on antiproliferative function in the PitNET cells. These findings suggested that SSA/DA treatment acted in a tumour suppressive manner and furthermore, collagen related interactions and pathways were enriched, implicating extracellular matrix involvement in this anti-tumour effect of drug treatment.